PENGARUH PROFITABILITAS DAN SOLVABILITAS TERHADAP AUDIT DELAY DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL PEMODERASI - Nuraini, Indah; Hadiyati, Siti Nur; Destiana, Rina (Universitas Muhammadiyah Tangerang, 2022)
Audit delay is defined as the length of time for the completion of the audit starting from the closing date of the financial year until the date of issuance of the financial statements. This study was conducted to provide empirical evidence of the effect of profitability and solvency on audit delay with firm size as a moderating variable. The sample of this study uses manufacturing companies in the consumer goods industry sector that are listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The data used are financial statements issued by the company every year. The sampling technique used purposive sampling method. This research uses multiple regression analysis method and moderated regression analysis with the MRA test approach. The results of this study indicate that solvency has an effect on audit delay, while profitability has no effect on audit delay and firm size is able to moderate the effect of solvency on audit delay, while firm size is unable to moderate the effect of profitability on audit delay.Keywords: Profitability, Solvency, Firm Size, Audit Delay